2021
DOI: 10.1186/s12879-021-06207-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for measles outbreak in Ataq and Habban districts, Shabwah governorate, Yemen, February to May 2018

Abstract: Background Recent conflict and war in Yemen lead to collapse of the health system, decrease of immunization coverage and spread of many outbreaks. On May 22, 2018, the surveillance officer in Shabwah governorate reported an increased number of suspected measles. On May 24, 2018, a team from Yemen-Field Epidemiology Training Program was sent to investigate. The aims were to describe the outbreak, determine the risk factors for measles infection and recommend control measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
1
7
1
Order By: Relevance
“…This outbreak investigation result is in line with a study conducted in southeastern Ethiopia, Yemen, and northeastern Ethiopia. 8 , 42 , 43 Evidences from previous studies conducted in India and Nigeria found a link between measles and malnutrition that malnourished children are more likely than well-nourished children to get severe measles infections. 2 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…This outbreak investigation result is in line with a study conducted in southeastern Ethiopia, Yemen, and northeastern Ethiopia. 8 , 42 , 43 Evidences from previous studies conducted in India and Nigeria found a link between measles and malnutrition that malnourished children are more likely than well-nourished children to get severe measles infections. 2 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…In all 5 studies, undernutrition significantly increased reported measles incidence by 1.7 to 24.9 times (OR: 1.7, 3.0, 3.0, 3.4, 24.9). (23,(44)(45)(46)48) 3 studies also found that measles was an important contributing factor to malnutrition, and that it could increase the risk of malnutrition threefold. (42,47,48) The evidence for an association between malnutrition and measles mortality is less consistent, though 6 out of 10 studies found a positive correlation between malnutrition and measles mortality.…”
Section: Undernutritionmentioning
confidence: 99%
“…aged 6 to 60 months) (95% CI: 1.9-329.6). (23) In Romania, reported measles cases were 3.4 times more likely than controls to have had a history of malnutrition (95% CI: 1.1-9.9). (45) In 2018, modelling from sub-national regions of Namibian aggregated measles incidence data from 2005 to 2014 found the risk of measles to be associated with the prevalence of underweight children under 5 years of age (95% CI: 0.0019, 0.1128).…”
Section: Findings On the Association Between Measles And Malnutritionmentioning
confidence: 99%
See 2 more Smart Citations